A recombinant Artemisia vulgaris pollen adjuvanted Art v 1 protein-based vaccine treats allergic rhinitis and bronchial asthma using pre- and co-seasonal ultrashort immunotherapy regimens in sensitized mice - Babayeva, Meruert; Tabynov, Kairat; Nurpeisov, Tair; Fomin, Gleb; Renukaradhya, Gourapura J.; Petrovsky, Nikolai; Tabynov, Kaissar (Frontiers in Immunology, 2022)
Allergic rhinitis is an important risk factor for bronchial asthma. Allergen-specific immunotherapy (ASIT) is the gold standard for treatment of allergic rhinitis, conjunctivitis, and asthma. A disadvantage of current ASIT methods is the length of therapy which requires numerous allergen administrations. The success of ASIT is determined by its schedule, which, depending on the vaccine and type of allergy, can be pre-seasonal (before the allergy season begins), combined pre/co-seasonal (during the allergy season) etc. The aim of the present study was to evaluate a vaccine based on recombinant Artemisia vulgaris pollen major Art v 1 protein formulated with ISA-51 adjuvant for therapy of allergic rhinitis and bronchial asthma in Artemisia-sensitized mice in an ultrashort (4 subcutaneous injections at weekly intervals) pre- and co-seasonal ASIT regimen. To simulate co-seasonal ASIT in mice, mice were regularly challenged with intranasal and nebulized Artemisia vulgaris pollen extract at the same time as receiving subcutaneous ASIT. For comparison, we used a previous Art v 1 protein vaccine formulated with SWE adjuvant, which in this study was modified by adding CpG oligonucleotide (Th1-biasing synthetic toll-like receptor 9 agonist), and a commercial vaccine containing a modified Artemisia vulgaris extract with aluminum hydroxide adjuvant. The therapeutic potential of Arv v 1 based vaccine formulations with different ASIT regimens was evaluated in high and low (10 times lower) dose regimens. The ISA-51-adjuvanted vaccine formulations were the only ones among those studied in the ultrashort pre- and co-seasonal ASIT regimens to provide significant reduction in both signs of allergic rhinitis and bronchial asthma in sensitized mice (vs. positive control). In the ISA-51 adjuvanted group, immune response polarization toward Th1/Treg was observed in pre-seasonal ASIT, as reflected in a significant decrease in the serum level of total and Art v 1-specific IgE and increased ratios of allergen-specific IgG2a/IgG1 and IFN-γ/IL-4. The high dose SWE-CpG-adjuvanted vaccine had similar efficacy to the ISA-51 adjuvanted groups whereas the commercial vaccine showed significantly less effectiveness. The findings support further preclinical safety studies of the Arv v 1-based vaccine formulated with ISA-51 adjuvant.